Late hierarchical societies in the Diquís delta, southeast of Costa Rica - Corrales, Francisco (2018)
In several regions of southern Central America the presence of chiefdoms has been proposed, based on different indicators and the ethnohistorical and ethnographic comparison. This article focuses on Diquís delta late occupations (AD 800-1550) where archaeological research has provided information about an increase in sites size, the presence of architecture and the production of prestige goods that can be associated with rank and power. The particularities of delta productivity, the association of the most complex sites with the best soils, the privileged position to obtain some resources (food, raw materials) suggests the preponderance of the economic in the generation of power by the leaders, although, we propose, there was also an important role of the specialization of craft production and the symbolic aspects related to prestigious objects such as stone spheres, gold ornaments, statuary and special ceramics. However, there are some limitations in the discussion, since much of the data are derived from activities with very general objectives. In the future, it is necessary to delve into information related to agricultural production and its eventual intensification, institutionalization of leadership, appearance of hierarchy and the factors of its consolidation in the delta, among other topics.